DO STRESS PERCEPTIONS MITIGATE THE LINKS BETWEEN POSITIVE AND NEGATIVE EMOTION VARIABILITY AND INFLAMMATION?. (11th November 2018) - Jones, D; Graham-Engeland, J; Smyth, J M; Sin, N; Almeida, D M; Sliwinski, M J; Engeland, C G
Abstract: Emotion variability (the extent to which individuals vary in emotional states over time) has been associated with poorer health indicators (e.g., dysregulated diurnal cortisol) but its associations with inflammation are unknown. In a diverse sample of participants (N=231; aged 25–65; 65% female; 62% Black; 25% Hispanic) we examined if positive emotion variability (PEV) and negative emotion variability (NEV) exhibited linear or curvilinear associations with a composite circulating inflammatory measure and C-reactive protein. Results suggested that PEV and NEV exhibit curvilinear associations with inflammation, with both high and low emotion variability being associated with higher inflammation, but only among older men. These results became non-significant after perception of stress was entered into the model. These data are the first of our knowledge to suggest that PEV and NEV may be associated with inflammation. Our results further suggest that favorable perceptions of stress may mitigate the link between emotional variability and inflammation.